n-Butanol production in S. cerevisiae: co-ordinate use of endogenous and exogenous pathways - Swidah, R. (Appl Microbiol Biotechnol, 2018)
n-Butanol represents a key commodity chemical and holds significant potential as a biofuel. It can be produced naturally by Clostridia species via the ABE pathway. However, butanol production via such systems can be associated with significant drawbacks. Therefore, substantial efforts have been made toward engineering a suitable industrial host for butanol production. For instance, we previously generated a metabolically engineered Saccharomyces cerevisiae strain that produces ~300 mg/L butanol from combined endogenous and exogenous pathways. In this current study, the endogenous and exogenous pathways of butanol production were further characterised, and their relative contribution to the overall butanol titre was assessed. Deletion of any single component of the exogenous ABE pathway was sufficient to significantly reduce butanol production. Further evidence for a major contribution from the ABE pathway came with the discovery that specific yeast deletion mutants only affected butanol production from this pathway and had a significant impact on butanol levels. In previous studies, the threonine-based ketoacid (TBK) pathway has been proposed to explain endogenous butanol synthesis in ADH1 mutants. However, we find that key mutants in this pathway have little impact on endogenous butanol production; hence, this pathway does not explain endogenous butanol production in our strains. Instead, endogenous butanol production appears to rely on glycine metabolism via an α-ketovalerate intermediate. Indeed, yeast cells can utilise α-ketovalerate as a supplement to generate high butanol titres (> 2 g/L). The future characterisation and optimisation of the enzymatic activities required for this pathway provides an exciting area in the generation of robust butanol production strategies.